Effect of Weed Management in Clusterbean under Dryland Conditions of Western Rajasthan: EFFECT OF WEED MANAGEMENT IN CLUSTERBEAN - Sumitra Devi Bamboriya; A.S. Jat; Rajkamal Dagar (Annals of Arid Zone, 2024)
On farm trials (OFTs) were conducted during kharif 2020 and 2021 at Dabra and Maulasar villages of Didwana tehsil of Nagaur district of Rajasthan with the objective to study the effect of weed management in clusterbean under dryland conditions of western Rajasthan. Four treatments of weed control i.e., weedy check, imazethapyr + imazamox (ready mix) 40 g ha-1 applied at 20 days after sowing (DAS), imazethapyr 50 g ha-1 applied at 20 DAS and weed free plot were imparted in this trial. Results showed that, crop in weed free condition recorded significantly higher growth parameters, yield attributes and seed yield (0.993 t ha-1) followed by application of imazethapyr + imazamox (ready mix) 40 g ha-1 applied at 20 DAS (0.948 t ha-1). The increase in grain yield due to application of imazethapyr + imazamox (ready mix) 40 g ha-1 applied at 20 DAS over the farmers’ practice (Imazethapyr 50 g ha-1applied at 20 DAS) was 9.22%. Application of imazethapyr + imazamox (ready mix) 40 g ha-1 applied at 20 DAS provided maximum net returns (Rs 49399 ha-1) and BC ratio of 3.27.